Proanthocyanidins supplemented diet alter anti-aging-markers and improved lifespan in Drosophila melanogaster model - Jaafaru, Mohammed Sani; Muhammad, Suleiman Alhaji; Mohammed, Zainab Kasim; Aliyu, Yakubu; Razis, Ahmad Faizal Abdull (SpringerOpen, 2024)
Background: It is unequivocally believed that phenolics and flavonoids from fruits and vegetables hold robust prevention potentials against age-related disease development through their abundant hydroxyl groups. This study explored the potential neuromuscular enhancement and anti-aging effects of dietary supplemented proanthocyanidins-rich fraction from Tamarindus indica on Drosophila melanogaster model. One- to three-day-old male and female D. melanogaster were fed with a proanthocyanidins-rich fraction-supplemented diet for 7 days at two different concentrations. Following the effective dose determination, longevity assay (rate of survival), behavioral assay (negative geotaxis and eclosion), and biochemical assays (aging and antioxidant enzymes activities) were conducted to assess the fraction’s longevity, antioxidant, and anti-aging effects on D. melanogaster model. Result: The results showed a significant (p < 0.05) improvement in the rate of emergence and lifespan of the flies fed with proanthocyanidins-rich fraction-supplemented diet at both concentrations (1.5 mg/g and 2.5 mg/g) compared to the normal control. A significant decrease in acetylcholinesterase (AChE) activity and the level of caspase-3 and caspase-9 were observed in the D. melanogaster flies fed with the fraction-containing diet when compared with the normal control. The supplemented diet also significantly increases the activity of catalase, superoxide dismutase (SOD), and glutathione-s-transferase (GST) in a concentration-dependent manner but not nicotinamide quinone oxidoreductase one (NQO1) in D. melanogaster upon comparison with the normal control. Conclusion: The observable changes in the experiment were attributed to the T. indica-derived proanthocyanidins, flavonoids with robust biological activities. The flavonoid-rich fraction proved its potential by enhancing the antioxidant system in D. melanogaster via the increase in the activities of some of the phase II antioxidant enzymes. The present study provides more insights into the wider perspectives of societies on the use of plant-derived natural compounds as the potential approach toward prevention against aging and age-related morbidities which enhance wellness and the quality of life in humans and animals.